An Experimental Biomechanical Study on Artificial Atlantoodontoid Joint Replacement in Dogs. Issue 1 (February 2017) - Zang, Quanjin; Liu, Yanming; Wang, Dengfeng; Li, Haopeng; Yang, Pinglin; Wang, Dong; He, Xijing
Abstract : Study Design: This study tested the biomechanics of artificial atlantoodontoid joint replacement (AAOJR) in a dog model. Dogs were divided into the artificial AAOJR group (n=10), the decompression group (n=10), and the healthy control group (n=10) using a random number table. Objective: To evaluate whether the use of AAOJR for repair of atlantoaxial instability retains rotation and restores stability. Summary of Background data: Atlantoaxial instability is characterized by excessive movement or laxity at the junction between the atlas (C1) and axis (C2). Pure decompression can lead to considerable loss of head and neck rotation and postoperative impairment. A series of biomechanical tests on cadavers found that the artificial AAOJR might rebuild the stability and retain the rotation function. Methods: We designed the AAOJ based on the radiologic and anatomic data of the dog atlas and axis, and established an animal model by resecting the odontoid and implanting the AAOJ into dogs. The biomechanical experiments measured the range of motion (ROM), neutral zone (NZ), and stiffness of flexion, extension, lateral bending, and axial rotation in the intact state, the decompressed state, after AAOJR, and after a fatigue test. Results: Compared with the intact state, after decompression operation, ROM and NZ in all directions, and stiffness during flexion were increased, and stiffness in all other directions was decreased. Compared with the after decompression state, AAOJR before and after the fatigue test resulted in decreased ROM in all directions (all P <0.05), decreased NZ during flexion/extension and lateral bending (all P <0.05), an increased NZ during axial rotation (both P <0.05), and increased stiffness in all directions (all P <0.05). Conclusions: These results indicate that AAOJR could reconstruct the vertebral stability of the C1–C2 segment and retain some axial rotation function.